Designs of seven grade schools built as wooden structures in period 1927–1938 on Lubelszczyzna region - Miłkowska, Ewa (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
In the interwar period, there was a clear hike in the interest in building public institutions in the Lublin region. Major war damage and the lack of a regulated school network in this area prompted the creation of numerous educational institutions. The authorities took special care to create a learning environment for the youngest students. Thus, primary schools of all types were erected, ranging from one-class schools in small communities to large seven-class facilities in towns and cities. Large wooden schools are particularly noteworthy. One hundred of them were built in the are. The design of most of them resembled a manor house. However, there is a group of buildings whose style refers to modernism. Although in the years 1918-1939 it was recommended to build seven-grade schools from bricks, these facilities were designed and built as wooden structures.